Let's solve your equation step-by-step.
−
18
+
y
=
6
(
2
−
3
y
+
10
)
+
y
Step 1: Simplify both sides of the equation.
−
18
+
y
=
6
(
2
−
3
y
+
10
)
+
y
−
18
+
y
=
(
6
)
(
2
)
+
(
6
)
(
−
3
y
)
+
(
6
)
(
10
)
+
y
(Distribute)
−
18
+
y
=
12
+
−
18
y
+
60
+
y
y
−
18
=
(
−
18
y
+
y
)
+
(
12
+
60
)
(Combine Like Terms)
y
−
18
=
−
17
y
+
72
y
−
18
=
−
17
y
+
72
Step 2: Add 17y to both sides.
y
−
18
+
17
y
=
−
17
y
+
72
+
17
y
18
y
−
18
=
72
Step 3: Add 18 to both sides.
18
y
−
18
+
18
=
72
+
18
18
y
=
90
Step 4: Divide both sides by 18.
18
y
18
=
90
18
y
=
5